2019
DOI: 10.1088/1361-6382/ab4707
|View full text |Cite
|
Sign up to set email alerts
|

Space test of the equivalence principle: first results of the MICROSCOPE mission

Abstract: The weak equivalence principle (WEP), stating that two bodies of different compositions and/or mass fall at the same rate in a gravitational field (universality of free fall), is at the very foundation of general relativity. The MICROSCOPE mission aims to test its validity to a precision of 10−15, two orders of magnitude better than current on-ground tests, by using two masses of different compositions (titanium and platinum alloys) on a quasi-circular trajectory around the Earth. This is realised by measuring… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
135
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(142 citation statements)
references
References 66 publications
7
135
0
Order By: Relevance
“…Parameter Current σ = 5 ppm σ = 1 ppm σ = 0.1 ppm w 0 0.14 0.16 0.15 0.11 ζ (ppm) 5.3 3.0 2.3 0.5 be available from the final MICROSCOPE results (Touboul et al 2019).…”
Section: Improving Constraints: Prospects and Limitationsmentioning
confidence: 99%
“…Parameter Current σ = 5 ppm σ = 1 ppm σ = 0.1 ppm w 0 0.14 0.16 0.15 0.11 ζ (ppm) 5.3 3.0 2.3 0.5 be available from the final MICROSCOPE results (Touboul et al 2019).…”
Section: Improving Constraints: Prospects and Limitationsmentioning
confidence: 99%
“…This was presented as an observed physical principle, without a deeper explanation. Newton and many later experimentalists have conducted different experiments to verify UFF, no deviations have been found that are larger than 1.3 × 10 −14 (Touboul et al 2019). This equivalence between the inertial and passive gravitational masses for test particles (defined here as objects with negligible gravitational selfenergy) is the so-called weak equivalence principle (WEP).…”
Section: Introductionmentioning
confidence: 97%
“…The equivalence stated in this way is based on another equivalence between passive-gravitational mass m G and inertial mass m I of a body (also known as the Galilean Equivalence Principle) which has been confirmed by a number of experiments (see [3,4] or [5] for a comprehensive review), most recently by the Eöt-Wash experiment [6] and the MICROSCOPE experiment [7,8]. If m G and m I were not equal, one would be able to perform local experiments (such as dropping test bodies) in the accelerating frame K ′ which would produce differences between the outcomes of the same experiments performed in the reference K.…”
Section: Introductionmentioning
confidence: 82%
“…where u are particles' 4-velocities and where for simplicity we used reparametrization invariance and set g u u = const. Compatibility with the Lorentz force requires that Equations 7and (8) both imply that h � A � A � = 0. Therefore either h � = 0 or we have A � A � = 0 which implies (A �2 ) ⋅ = 0 and hence A �2 = const.…”
Section: Classical Constraintsmentioning
confidence: 99%